2021
DOI: 10.1080/14787210.2022.1997587
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of pharmacological interventions on mortality and the average length of hospital stay of patients with COVID-19: a systematic review and meta-analysis of randomized controlled trials

Abstract: Introduction Up to now, numerous randomized controlled trials (RCTs) have examined various drugs as possible treatments for Coronavirus Disease 2019 (COVID-19), but the results were diverse and occasionally even inconsistent with each other. To this point,we performed a systematic review and meta-analysis to assess the comparative effectiveness of pharmacological agents in published RCTs. Areas covered A literature search was performed using PubMed, SCOPUS, EMBASE, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 141 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…Early control of cytokine storm by anti-inflammatory treatments may improve the survival rate of patients with COVID-19. 34 It is well-known that pretreatment of human macrophages with estrogen can reduce tumor necrosis factor alpha (TNF-α) expression by inhibiting nuclear factor-kappa B (NFk-B) and JAK2 signaling pathways. 35 Estrogen also attenuates monocyte and macrophage recruitment by downregulating the expression of chemokine ligand 2 during inflammation and dampening toll-like receptor 4-mediated NFk-B activation.…”
Section: Discussionmentioning
confidence: 99%
“…Early control of cytokine storm by anti-inflammatory treatments may improve the survival rate of patients with COVID-19. 34 It is well-known that pretreatment of human macrophages with estrogen can reduce tumor necrosis factor alpha (TNF-α) expression by inhibiting nuclear factor-kappa B (NFk-B) and JAK2 signaling pathways. 35 Estrogen also attenuates monocyte and macrophage recruitment by downregulating the expression of chemokine ligand 2 during inflammation and dampening toll-like receptor 4-mediated NFk-B activation.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review evaluating the effects of five pharmacologic interventions (i.e., anti‐inflammatory, antiviral, antiparasitic, antibody, and antibiotics) on the length of hospital stay showed that anti‐inflammatory (mean difference (MD) −1.41; 95%CI, −1.75, −1.07) and antiparasitic drugs (MD −0.65; 95%CI, −1.26, −0.03) significantly reduced the length of hospital stay 149 . However, in the present study we did not find any significant differences between the tocilizumab and control groups, in terms of the length of hospital stay or ICU stay ( p > 0.05).…”
Section: Discussionmentioning
confidence: 99%